2019
DOI: 10.1021/acssuschemeng.9b06179
|View full text |Cite
|
Sign up to set email alerts
|

Novel Silica Filled Deep Eutectic Solvent Based Nanofluids for Energy Transportation

Abstract: Liquid range of nanofluids is a crucial parameter as it intensively determines their application temperature scope. Meanwhile, improved thermal conductivity and stability are of great significances and comprise the main fundamental research topics of nanofluids. In this work, 2butoxy-3,4-dihydropyran (DP), produced from a convenient one-pot three-component reaction in water, was employed as dual lipophilic brusher and metal nanoparticle anchor. It was found that DP was able to enhance the dispersing ability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Almost all the above-described studies have confirmed that the dispersion of nanoparticles improves thermal conductivity in the DESs. By comparing the experimental data of [four] studies, it is revealed that the difference between the total thermal conductivity alterations is J o u r n a l P r e -p r o o f related to the type of solvent [96] and/or the type of nanoparticle [85]. The majority of results proved that an increase in temperature and the concentration of nanoparticles provide higher thermal conductivity in the prepared nanofluids in comparison with the pure DES.…”
Section: Experimental Studies On Using Des As Base Fluidmentioning
confidence: 98%
See 1 more Smart Citation
“…Almost all the above-described studies have confirmed that the dispersion of nanoparticles improves thermal conductivity in the DESs. By comparing the experimental data of [four] studies, it is revealed that the difference between the total thermal conductivity alterations is J o u r n a l P r e -p r o o f related to the type of solvent [96] and/or the type of nanoparticle [85]. The majority of results proved that an increase in temperature and the concentration of nanoparticles provide higher thermal conductivity in the prepared nanofluids in comparison with the pure DES.…”
Section: Experimental Studies On Using Des As Base Fluidmentioning
confidence: 98%
“…As another example, Liu et al [96] developed a typical preparation procedure to form a DES-based nanofluid by a combination of silica nanoparticle and glycerol:ChCl. According to this method, 100 ml of DES was mixed with a certain mass fraction of silica nanoparticle, and then the resulting combination was stirred for 2 hours at 353 K, subsequently, it was cooled to reach room temperature.…”
Section: -1 Preparation Des-based Nanofluidsmentioning
confidence: 99%
“…[234,235] Besides, pore generators of PLs provide an alternative capsule to encapsulate phase-change materials (PCMs) to improve the photothermal conversion performance. Besides, the accessible cavities of pore generators in PLs also provide a favorable space to incorporate nanoparticles with specific functions (e.g., magnetism, photothermal response), [219] thus realizing the synergy of photothermal conversion performance and specific function. However, till now, there are no studies of PLs available for thermal management in photo-thermal conversion applications.…”
Section: Thermal Managementmentioning
confidence: 99%
“…(Reproduced with permission. [219] Copyright 2019, American Chemical Society). and silica NIMs, and so on.…”
Section: Other Potential Applicationsmentioning
confidence: 99%
See 1 more Smart Citation